Biofabrication of 3D-printed, pre-cross-linked alginate dialdehyde–gelatin (ADA–GEL) scaffolds for an in vivo metastatic arteriovenous loop tumor model - Sandor, Evelin; Karimi, Tannaz; Schmid, Rafael; Kulicke, Yvonne; Heltmann-Meyer, Stefanie; Eckert, Carolin; Schmidt, Sonja K.; Röder, Jonas; Heppt, Markus V.; Boccaccini, Aldo R.; Horch, Raymund E.; Boßerhoff, Anja K.; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Vascularized models mimicking tumor pathophysiology to investigate tumor characteristics are of high interest. The arteriovenous loop (AVL) model is an established method to vitalize bioengineered tissue grafts. In this model, an artificial vascular axis serves as the only connection between the living organism and the biomaterial. The objective of this study was to establish a three-dimensional (3D) printed, functional scaffold design for the AVL rodent model, in which human melanoma cells, derived from lymph node metastasis, are embedded in pre-cross-linked alginate dialdehyde-gelatin (ADA–GEL) and implanted in rats (N = 10) for 4 weeks. Bioink scaffolds were 3D-printed in two different shapes (n = 5), designed specifically for the AVL model’s isolation chamber. Before implantation, the swelling behavior of the biofabricates was analyzed in vitro. The biocompatibility of the pre-cross-linked ADA–GEL and the impact of the scaffold-morphology were examined through macroscopic analysis and immunohistological stainings. The fluid uptake ratio of the hydrogel resulted in size extension, a finding which is highly relevant for the AVL model’s closed system. Biofabricated scaffolds made of pre-cross-linked ADA–GEL remained stable in vivo and allowed for de novo fibrovascular tissue formation. The hypothesized biocompatibility of the analyzed hydrogel was confirmed. The two scaffold models exhibited differences regarding tumor growth and de novo fibrovascular tissue formation capacity. In both groups, metastatic cells were detected in the lymph nodes of rodents. The present study demonstrated that the AVL model is an excellent in vivo tool for melanoma research, combining biofabrication and vascularization with a high ability to replicate metastasis. At the same we conclude, that adapting the design of the biofabricated implants to the AVL model, depending specifically on the ink used, is of major importance.